Linkages between poverty, food security and undernutrition: Evidence from China and India - de Brauw, Alan; Suryanarayana, M. H. (Emerald Publishing Limited, 2015)
– China and India are two of the fastest growing economies in the world, and poverty reduction has been substantial in both countries through the past few decades. Yet they have very different profiles in terms of food security and undernutrition – while at the micro-level China has performed well in terms of undernutrition, India has not. The purpose of this paper is to examine linkages between poverty, food security, and undernutrition in both countries.– In this paper, the authors discuss the linkages between poverty, food security, and undernutrition at the micro level, describe the literature, and make inferences for targeting the remaining poor, food insecure, or undernourished in both countries.– In China, there is a need for better tools for targeting the poor or malnourished. In India, more effective state-level policies should be better understood by the central government and disseminated to less successful states.– In this paper, the authors describe data sources on poverty, food security, and undernutrition in both China and India, and correlates with changes in all three. The authors try to understand what factors appear to lead to reductions in all three, pointing out data gaps in both countries.